Sìl′s′ke samovrâduvannâ za volos′kim pravom u Galičinì (XIV-XVIII st.) - Šandra, Roman (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The present article is dedicated to the organization of lосаl home-rule according to Walachian law, which was widely spread and implemented on the territory of Galicia during the ХІVth — ХVІІІth centuries. Walachian law regulated the relationship of rural self-government, court, tax payments and duty accomplishments, etc. In the article the first attempt was made to entirely define the system of organs of rural self-government according to Walachian law, analyse the process of its development, research the order of its formation and legal status, and also look into the power of certain authorities that were in the body of rural government.
Keywords: Galicja (XIV-XVIII w.); prawo wołoskie; samorząd wiejski